171k views
4 votes
Use the tables below to find (p − q)(2) (p – q)(2) =

2 Answers

5 votes

Answer:

the answer is 5 thank u very much

Explanation:

User Waveter
by
5.9k points
6 votes

Answer: ( p - q)(2)(p - q )(2) = 4 p² - 8 p q + 4 q²

Explanation:

We have expression ( p - q ) (2) ( p - q ) (2)

Here all the parenthesis are in multiplication .

First we multiply the constant 2 with the terms inside the parenthesis ( p - q) ,

we get

( 2p - 2 q) ( p - q) (2)

= ( 2p - 2q ) ( 2p - 2q)

Now we need to multiply the two parenthesis together using FOIL method .

( 2p - 2q ) ( 2 p - 2q )

= 2 p ( 2 p - 2 q ) - 2q ( 2p - 2q )

= 2p * 2p - 2p * 2q - 2q * 2p + 2q * 2q

= 4p² - 4 p q - 4 p q + 4 q²

Combining like terms , we get

4p² - 8 pq + 4q²

User Pratikm
by
5.4k points